The Influence Of Green Marketing Implementation On Consumer Satisfaction At Dhoplang Market, Pandan Village, Slogohimo District, Wonogiri Regency - Adhelia Nurul Fitri, Zhylma; Mashudi, sugengh; Kristiyana, Naning; Chamidah, Siti (Jurnal Ekonomi, 2024)
Purpose: This study aims to investigate how the implementation of green marketing affects consumer satisfaction at Dhoplang Market, Pandan Village, Slogohimo Subdistrict, Wonogiri Regency.Green Marketing in this study consists of 4 components, that is green product, green price, green place and green promotions. This study includes independent variables consisting of green product, green price, green place and green promotion and consumer satisfaction as the dependent variable. Methodology/approach: This study is a quantitative study. Information was obtained from data collection originating from questionnaire questions distributed to respondents and also through field observations with a sample size of 85 respondents. A purposive sampling technique was used to determine the sample.. Using multiple linear regression for data analysis in SPSS version 25. Results/findings: Consumer satisfaction is positively and significantly influenced by environmentally friendly products, positively and significantly influenced by environmentally friendly prices, positively and significantly influenced by environmentally friendly places, but not significantly influenced by environmentally friendly promotions. These four components make a major contribution to implementing green marketing to increase consumer satisfaction at Dhoplang Market. Limitations: This study's sampling is still insufficient, which is a restriction; hopefully, a larger sample will be used in subsequent studies. Contribution: This research can help market managers and business actors in determining effective strategies to increase consumer satisfaction.